Transportasi Pajak dan Implikasinya terhadap Kepatuhan Wajib Pajak - Addina Al Qoyyimah; Mhd. Ridho Akbar (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study aims to analyze the relationship between the tax transportation system and the level of taxpayer compliance. In the context of tax administration modernization, tax transportation refers not only to physical mobility but also to the efficient mechanism of digitalization and distribution of tax information. The implications of an effective tax transportation system include increased transparency, easy access to tax information, and acceleration of the reporting process. This study examines how optimizing tax infrastructure, such as online reporting systems, mobile tax education, and integration between agencies, can encourage voluntary and formal compliance levels. Data were obtained through a quantitative approach by distributing questionnaires to individual and corporate taxpayers in several major cities. The results of the analysis show that there is a significant positive correlation between tax transportation efficiency and taxpayer compliance. This study recommends strengthening the tax information and technology system as a strategic step in improving national tax compliance.